What Big Teeth You Have: An Educational Approach to Wolf Conservation - Brinker, Nastassja (ProQuest Dissertations & Theses, 2015)
As the subject of deep-seated cultural and historical antipathies and revulsion, the wolf presents a unique challenge for wildlife educators working to promote its conservation and value as a species while they are forced to combat the systematic persecution and eradication it has suffered historically across North America. This project used a series of ethnographic interviews and on-site observations to examine how the Northern Lights Wildlife Wolf Centre employs conservation through education strategies by means of its interpretive program, firsthand exposure to wolves, and other messaging platforms to affect attitude changes in visitors towards wolves. This study also examines how attitude change has the potential to encourage long-term pro-environmental behaviour and advocacy for wolf conservation practices.